EQUATIONS INVOLVING THE INTEGER PART OF A REAL NUMBER - Tilagova Buvgilos Saidkulovna; Ganiyeva Dilrabo Aliyevna (The American Journal of Applied Sciences, 2024)
This study explores the role and implications of the integer part of real numbers, represented by the floor function (⌊x⌋), in various mathematical fields. The research examines its applications in number theory, approximation theory, algorithm design, and more. By analyzing existing literature and theoretical frameworks, this paper aims to illuminate the significance of the floor function in solving equations and understanding mathematical phenomena.